Ocorrência de infecção pelo vírus da hepatite e em pacientes pós transplante renal em um hospital terciário de São Paulo-SP - Passarini, Amanda [UNIFESP] (2018)
Objective: To verify the occurrence of renal transplant seroconversion in patients performing this procedure at Hospital do Rim / UNIFESPSP, from November / 2016 to August 2017. Methods: 371 candidates for organ donation and 441 patients submitted to renal transplantation, attended from November 2016 to August 2017. Blood samples were tested by antiHEV IgG and IgM serology, as well as the realtime RTPCR screening of HEVRNA. Results: The prevalence of hepatitis E virus infection in the study population was 15.5% (126/816), the majority of males with a mean age of 46 years. We later evaluated patients who were not antiHEv IgG reagents at the time of transplantation to evaluate posttransplant seroconversion. A total of 36 (18.2%) patients underwent seroconversion to antiHEV IgG, on average 111 days after transplantation, of which 4 (2%) were HEV positive. Most seroconversions occurred in men (55.6%) and the mean age of these patients was 45.1 years. We analyzed the type of donor among these patients, and 78% received a deceased donor organ (28/36) and the donor antiHEV IgG positivity of the donors, the majority received organ from a nonreactive donor (83.3%). We evaluated some variables that could be associated with seroconversion, the most used immunosuppression was Tacrolimus (86.4%), only one patient had a blood transfusion, 1.02% had ALT alterations, 86% had creatinine alterations and 80% were reagent for CMV. These variables were not correlated with seroconversion. Conclusion: These are the first data on seroconversion in patients undergoing renal transplantation in Brazil. It was possible to demonstrate a seroconversion in 18.2% of patients, on average 111 days after transplantation. We suggest that this could be a secondary infection (reactivation), indicating that the hepatitis E virus could be latent in the recipient's kidney, reactivating at the time of greater immunosuppression or even in the kidney that he is receiving, which is a primary infection , transmitted at the time of transplantation by the donor. More studies are needed to establish which is the main route of infection for kidney transplant recipients.